Genome-Wide Identification Reveals That Nicotiana benthamiana Hypersensitive Response (HR)-Like Lesion Inducing Protein 4 (NbHRLI4) Mediates Cell Death and Salicylic Acid-Dependent Defense Responses to Turnip Mosaic Virus - Wu, Xinyang; Lai, Yuchao; Rao, Shaofei; Lv, Lanqing; Ji, Mengfei; Han, Kelei; Weng, Jiajia; Lu, Yuwen; Peng, Jiejun; Lin, Lin; Wu, Guanwei; Chen, Jianping; et al. (Frontiers in Plant Science, 2021)
Hypersensitive response (HR)-like cell death is an important mechanism that mediates the plant response to pathogens. In our previous study, we reported that NbHIR3s regulate HR-like cell death and basal immunity. However, the host genes involved in HR have rarely been studied. Here we used transcriptome sequencing to identify Niben101Scf02063g02012.1, an HR-like lesion inducing protein (HRLI) in Nicotiana benthamiana that was significantly reduced by turnip mosaic virus (TuMV). HRLIs are uncharacterized proteins which may regulate the HR process. We identified all 6 HRLIs in N. benthamiana and functionally analyzed Niben101Scf02063g02012.1, named NbHRLI4, in response to TuMV. Silencing of NbHRLI4 increased TuMV accumulation, while overexpression of NbHRLI4 conferred resistance to TuMV. Transient overexpression of NbHRLI4 caused cell death with an increase in the expression of SA pathway genes, but led to less cell death level and weaker immunity in plants expressing NahG. Thus we have characterized NbHRLI4 as an inducer of cell death and an antiviral regulator of TuMV infection in a SA-mediated manner.